RADIKALISASI DEMOKRASI: CATATAN PENGANTAR - Wahyudi, Agus (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2014)
This article aims to introduce a way of thinking, a perspective, which is expected to be useful for our reading on the complexity of social world in our age, and further to encourage change and transformation of social structures which allow mediate social injustice. We need to understand position of the pespective we will be discussing within the general category of scientific knowledge, before we are able to discuss the notion of democracy radicalization in further detail and why we need to talk about this idea.